Analysis of zirconium containing materials using multiple digestion and spectrometric techniques - Lotter, Steven James (University of the Free State, 2014)
The preparation of pure zirconium metal for nuclear applications is difficult due to the non-reactivity of zirconium minerals, such as zircon. The ability to accurately analyse zirconium-containing materials across the whole beneficiation chain is of crucial importance to the zirconium industry as a whole. The development of such an analytical technique is problematic, however, as the very properties which make these materials desirable also make quantification of their components extremely difficult. Certified reference materials for the fluoride-containing Necsa zirconium process products were not available. Therefore in-house reference materials were created by crystallisation of several (cation)xZrF4+x compounds. Potassium catena di-μ-fluorido-tetrafluoridozirconate(IV), cesium hexafluoridozirconate(IV) and tetraethyl ammonium catena di-μ-fluorido-bis-(trifluoridozirconate(IV)) monohydrate were prepared and characterised by X-ray crystallography and qualitative XRD. Coordination numbers for the zirconium atoms in each of these crystals were found to be 8, 6 and 7 respectively. Bridging fluorine bond lengths were determined to be approximately 2.06 and 1.97 Å for the potassium and tetraethyl ammonium complexes while terminal bond lengths were found to be 2.17 (potassium), 2.007 (cesium) and 2.15 (tetraethyl ammonium) Å. ICP-OES lower limits of detection for zirconium in the 3.25% nitric acid matrix were found to be 1.6 ppb with lower limits of quantification being ten times this value. ICP-OES zirconium recoveries for these crystals were 101(1) and 100(2)% for the potassium and cesium crystals respectively. Dissolution of various commercial and Necsa process samples was problematic and thus several digestion methods were investigated. Sulphuric acid, ammonium bifluoride and hydrofluoric acid were all investigated along with microwave assistance. A microwave-assisted acid digestion method was developed capable of complete dissolution of all zirconium compounds with ICP-OES analytical recoveries of 102.0(9), 100(2) and 101(3)% for 99.98% zirconium metal foil, ZrC and ZrH2 respectively. In order to circumvent the dissolution step a solid state GD-OES method was developed wherein sample powders were pressed into disks with a binder material, either copper or graphite. Initially instrument response across different samples was inconsistent but after optimisation of several instrument parameters, such as applied voltage and pre-burn time, a calibration curve with a R 2 value of 0.9805 was achieved using multiple sample materials. This was achieved using the radio frequency glow discharge source operating at 900 V applied voltage and 14 W applied power with a 5-minute pre-burn period. Results for Necsa process products were largely in line with those achieved by the ICP-OES method.

Die voorbereiding van suiwer sirkoniummetaal vir aanwending in die kernindustrie is problematies as gevolg van die onreaktiwiteit van sirkoniumminerale, soos sirkoon. Die vermoë om sirkonium-bevattende materiale akkuraat tydens die hele veredelingsproses te ontleed, is van kardinale belang vir die totale sirkonium-industrie. Die ontwikkeling van sulke analitiese tegnieke is moeilik, aangesien die eienskappe wat hierdie verskillende sirkoonverbindings materiaal aantreklik vir die industrie maak, ook die kwantifisering van hul komponente baie bemoeilik. Gesertifiseerde verwysingsmateriaal (GVM) vir die fluoried-bevattende Necsa sirkonium proses produkte was nie beskikbaar nie. Daarom is GVM’s in die vorm van verskeie (katioon)xZrF4+x verbindings in die laboratorium berei. Kalium catena di-μ-fluorido-tetrafluoridosirkonaat(IV), sesium heksafluoridosirkonaat(IV) en tetraetiel ammonium catena di-μ-fluorido-bis-(trifluoridosirkonaat(IV)) monohidraat is voorberei en met behulp van X-straal kristallografie en kwalitatiewe XRD gekarakteriseer. Koördinasie getalle vir die sirkonium-atome is onderskeidelik as 8, 6 en 7 bepaal. Gebrugde Zr-F bindingslengtes van 2.06 en 1.97 Å is vir die kalium- en tetraetiel ammonium komplekse bepaal terwyl die terminale bindinglengtes as 2.17 (kalium), 2.007 (sesium) en 2.15 (tetraetiel ammonium) Å bepaal is. Die IGP se laagste vlakke van deteksie van sirkonium is in 3.25% salpetersuur matriks as 1.6 dpb bepaal terwyl laagste vlakke van kwantifisering as 16 dpb bereken is. Die sirkoniumherwinning in die kalium- en sesiumkristalle is met behulp van die IGP as 101(1) en 100(2)% bepaal. Ontbinding van verskeie kommersiële en Necsa prosesmonsters was problematies en is met behulp van verskeie verteringsmetodes ondersoek. Mikrogolfvertering met behulp van swawelsuur, ammoniumbifluoried en fluoorsuur is in hierdie deel van die studie ondersoek. 'n Mikrogolf-ondersteunde suurverteringsproses is ontwikkel. Hierdie nuwe metode was in staat om volledig alle sirkoniumverbindings te ontbind en te bewerkstellig met IGP analitiese resultate van 102.0(9), 100(2) en 101(3)% vir die 99.98% sirkonium metaalfoelie, ZrC en ZrH2 is onderskeidelik verkry. Om die verteringsstap van die verskillende verbindings te omseil, is 'n vaste toestand GD-OES metode ontwikkel waartydens monsterpoeiers in skywe, in die teenwoordigheid van 'n bindingsmateriaal soos koper of grafiet, gedruk is. Aanvanklike kalibrasieresultate wat met verskillende monsters uitgevoer was, was teenstrydig. Tydens die optimalisering van verskeie instrumentparameters, soos byvoorbeeld die spanning en aanvanklike voorbrandingstye, is 'n kalibrasie met 'n R 2 waarde van 0.9805 met behulp van verskeie sikoonbevattendeverbindings verkry. Hierdie resultate is verkry deur van die radiofrekwensie gloeiontladingsbron by toegepaste spanning van 900 V, 'n toegepaste drywing van 14 W en 'n aanvanklike voorbrandingstyd van 5 minute gebruik te maak. Analitiese resultate vir die sirkooninhoud van verskeie Necsa-proses produkte was grootliks in lyn met dié wat deur die IGP metode verkry is.
Thesis (Ph.D. (Chemistry))--University of the Free State, 2014
Keywords: Zircon; Mineral; Digestion; Zirconium; Hafnium; Analysis; Determination; Quantification; Trace; Impurities; Fusion; Microwave; Inductively coupled plasma optical emission spectroscopy (ICP-OES); Inductively coupled plasma mass spectrometry (ICP-MS); Glow discharge optical emission spectroscopy (GD-OES); Zirconium alloys